Assessing Pressure Injury Knowledge Using the Pieper-Zulkowski Pressure Ulcer Knowledge Test. (September 2018) - Delmore, Barbara; Ayello, Elizabeth A.; Smart, Hiske; Sibbald, R. Gary
ABSTRACT: OBJECTIVE: To determine the pressure injury knowledge of health professionals before and after providing an interactive, educational intervention. DESIGN AND SETTING: The research design was a quasi-experimental study using a nonrandomized pretest/posttest methodology in Manila, Philippines. PATIENTS AND INTERVENTION: The population for this study was healthcare professionals who participated in a 2-day Basic WoundPedia course. There were 57 participants on day 1 and 55 participants on day 2. The Pieper-Zulkowski Pressure Ulcer Knowledge Test (PZ-PUKT, version 2), a standardized, validated instrument with 72 items, was used to measure 3 domains: prevention (28 items), staging (20 items), and wounds (24 items). The test was used to determine the baseline pressure injury knowledge of the students on day 1 before the course began and on day 2 after related content was completed. The intent of this approach was to document that knowledge deficits were met, especially for future courses. MAIN RESULTS: There was a statistically significant increase in pressure injury knowledge scores after healthcare professionals received an interactive, educational intervention. CONCLUSIONS: Measuring knowledge before and after educational intervention should be considered to determine whether knowledge deficits are corrected. This methodology reinforced the adult learning theory and to help participants realize their own knowledge deficits. The PZ-PUKT may prove a valuable nonthreatening instrument for adult learners to self-identify, self-learn, and self-correct knowledge according to the best new evidence as it becomes available. These findings documented that this interactive, educational intervention did improve the percentage of correct pressure injury knowledge concepts for this group in all 3 subscales. This study also added support for the newly revised PZ-PUKT.